Prevalence, mortality, and aetiology of paediatric shock in a tertiary hospital in Malawi: A cohort study. - Mercy Kumwenda; Roxanne Assies; Gloria Chathima; Harriet Khofi; Job B M van Woensel; Yamikani Chimalizeni; Josephine Langton; Job C J Calis (Public Library of Science (PLoS), 2024)
Shock is considered one of the most important mechanisms of critical illness in children. However, data on paediatric shock in sub-Saharan Africa is limited, which constrains development of effective treatment strategies. We aimed to describe the prevalence, mortality, and aetiology of paediatric shock in a tertiary hospital in Malawi. Children aged two months to 16 years presenting with shock (FEAST criteria; respiratory distress and/or impaired consciousness, and at least one sign of impaired circulation; capillary refill>3 seconds, cold extremities, weak pulse, or severe tachycardia) to the emergency department were included and followed-up prospectively using routinely collected data between February 2019 and January 2020. Prevalence, mortality and aetiology of shock were reported for both the FEAST criteria and World Health Organization (WHO) definition. The association between aetiology and mortality was assessed with univariable analysis. Of all screened admissions (N = 12,840), 679 (5.3%) children presented with shock using FEAST criteria and the mortality was 79/663 (11.9%). WHO-defined shock applied to 16/12,840 (0.1%) and the mortality was 9/15 (60.0%). Main diagnoses were viral/reactive airway diseases (40.4%), severe pneumonia (14.3%), gastroenteritis (11.3%) and presumed sepsis (5.7%). Children diagnosed with presumed sepsis and gastroenteritis had the highest odds of dying (OR 11.3; 95%-CI:4.9-25.8 and OR 4.4; 95%-CI:2.4-8.2). Considering the high mortality, prevalence of paediatric shock (FEAST and WHO definitions) in Malawi is high. Sepsis and gastroenteritis are diagnoses associated with poor outcome in these children. Consensus on a clinical meaningful definition for paediatric shock is essential to boost future studies.